(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
Synthesis of wide variety of substituted 1, 8-dioxo-octahydro xanthene derivatives from reacting various Benzaldehydes with 5, 5-dimethyl-1,3-cyclohexane-dione via Bismuth Nitrate [Bi(NO3)3 5H2O] Catalysed reaction is described. The present methodology offers several significant advantages such as high yields, short reaction times, simple operation and convenient work-up.